Potensi Pengembangan Hutan Bakau Takkalala Sebagai Kawasan Wisata Di Kecamatan Sinjai Timur Kabupaten Sinjai - Nurul Albab; A.Afif Zuhdi AR (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2023)
The tourism potential in East Sinjai District is quite a lot, one of which is the Takkalala Mangrove Forest Tourism which is located in the village of Sanjai. With the existence of these tourist destinations, East Sinjai District is a sub-district that contributes to local revenue from the tourism sector. East Sinjai District must improve itself, not only to increase the regional income of Sinjai Regency but also to develop Mangrove Forest Tourism facilities. The development of facilities is expected to be able to attract tourists to visit so that they can become a source of income in improving the local community's economy. The method used in this study is qualitative research, this research was conducted using the observation method, interviews by conducting direct interviews to obtain information at the research location. The results of the research are dividing the location into 2 zones; zoning of reception area and zoning of Mangrove Forest area. In terms of research on the zoning of the reception area there are facilities and infrastructure in the Takkalala mangrove forest tourism area that need to be provided while the Mangrove Forest area zoning needs additional bridges to access visiting tourists and the need for reforestation so that it can attract tourists to visit the Takkalala Mangrove Forest Tourism.